A national framework for breast cancer control: A report on Rwanda's inaugural symposium on the management of breast cancer. (December 2015) - Murthy, Shilpa Shree; Tapela, Neo; Muhimpundu, Marie Aimee; Balinda, Jean Paul; Musabyemariya, Florence; Kirby, Katie; Pace, Lydia E.; Riviello, Robert; Ntirenganya, Faustin; Ntakiyiruta, Georges
Highlights: A description of Rwanda's inaugural breast cancer symposium. A framework was developed which describes ways in which to approach a national breast cancer control program. Potential solutions and framework that arose may serve as a model for other low and middle income countries. Abstract: Breast cancer (BC) is on the rise and is a leading cause of cancer-related mortality for women globally. A highly treatable and survivable cancer in high-income countries, outcomes for BC in low- and middle-income countries (LMICs) are extremely poor. These inequities are often due to resource limitations within the health care system. Recognizing the gaps in care, the ministry of health and health care providers in Rwanda formed multi-disciplinary, cross-institutional collaborations to strengthen the health care system for BC patients. They implemented Rwanda's inaugural symposium on the management of breast cancer. Training and education, care delivery, patient-centered care, research and technology were underlying themes, which arose from the conference and serve as a framework that is integral in improving clinical outcomes. The multi-disciplinary collaborations, framework that arose from the major themes, and potential solutions that were developed from the symposium may serve as a model for other LMICs as they start to develop their own breast cancer control programs.